CRITERIA FOR THE COURT’S COMPLIANCE WITH THE OBLIGATION TO PROVIDE JUSTIFICATION OF ITS DECISIONS - Deshko, Lyudmyla (Teisė, 2016)
The article aims to identify the criteria of ‘the court’s compliance with the obligation to provide justification of its decisions. The following criteria have been identified: a court accepted the party’s (parties’) argument that has the following features: is concrete; is relevant; is appropriate; in case of court’s refusal to accept the evidence provided by the party (parties), the court provides detailed and compelling reasons for this refusal listed in its decision document; the evidence was admitted in a fair way; the evidence was examined in a fair way; implications of evidence examination and application of judicial norms are in compliance with CPHRFF; the procedural decision-making is fair.